Insights Into University Knowledge Transfer in the Social Sciences and Humanities (SSH) and Other Scientific Disciplines – More Similarities Than Differences - Hayden, Markus C.; Weiß, Martin; Pechriggl, Alice; Wutti, Daniel (Frontiers in Research Metrics and Analytics, 2018)
Knowledge transfer from universities to other portions of society is highly relevant in both academia and public policy. However, the focus on high-quality research outputs has forced researchers to concentrate their efforts mainly on ‘science-to-science’ achievements. Knowledge transfer activities are usually reduced to topics that are associated with university-industry collaboration or the exploitation of research results, such as procurement of patents. Achievements in fields characterized by ‘science-to-professionals’ and ‘science-to-public’ knowledge transfer are often not appreciated, but rather evaluated as extraordinary and voluntary contributions. Therefore, these are deemed as not beneficial for progression in academic careers. Furthermore, study of such aspects of knowledge transfer has rarely been conducted. While the reduction of knowledge transfer to profit-oriented indicators should in general be questioned, such an objective is particularly inappropriate in the social sciences and humanities (SSH). In the current study, we explored whether researchers themselves have a differentiated understanding of knowledge transfer and which attitudes towards knowledge transfer can be described. We also investigated motivators and obstacles associated with knowledge transfer itself. To analyze differences between the SSH and other scientific disciplines, we compared SSH researchers with those of other fields. Our sample consisted of 283 participants from 18 different Austrian universities. Results indicate that researchers possess a comprehensive understanding of knowledge transfer that is closely related to science-to-public and science-to-professionals disciplines, as well as university instruction. Importantly, issues regarding the exploitation of research results were questioned and motivators were linked to moral rather than economic issues. Within the scientific community, knowledge transfer is insufficiently appreciated and is not beneficial for progress in an academic career. As such, researchers are hindered in participating in knowledge transfer activities. Differences between SSH and non-SSH researchers were noted in several evaluated categories, but were mainly small in effect size. Both subsamples answered consistently along the same trend, indicating that the differences are smaller than we hypothesized. Our findings are critically discussed, and implications are extrapolated.